Contradição em uma pesquisa na graduação em Pedagogia: contribuições da abordagem sócio-histórico-cultural - Carrijo, Viviane Letícia Silva (2017)
The objective of this study was to understand the contradictions generated in the process of this research in a Study Group, composed of this researcher and seventeen students of a Pedagogy course of a private higher education institution, located in the East Zone of São Paulo. Specifically, it aimed to identify and discuss: 1a. contradictions that emerged from the planned and the accomplished proposals; and 1b. contradictions that emerged in the movement of the Study Group, regarding the participants’ education and reading views. Anchored in the Socio-Historical-Cultural Activity Theory (VYGOSTKY, 1930, 1934; LEONTIEV, 1977, 1978; ENGESTRÖM, 1999, 2009), this study emphasized: contradiction as constituent of the human activity’s dialectical movement (ENGESTRÖM, 1987, 1999); language and reading in the Socio-Historical-Cultural Perspective (BAKHTIN; VOLOSHIVOV, 1929; VYGOTSKY, 1934); and Social Activity (LIBERALI, 2009, 2012) and Multiliteracies (NEW LONDON GROUP, 1996; COPE; KALANTZIS, 2009; LIBERALI et al., 2015). Methodologically, this study was anchored in the Collaborative Critical Research (MAGALHÃES, 2011, 2012, 2014), an intervention research, marked by the reflexive-critical process, permeated by contradictions. The data were analyzed by the categories of Argumentation, according to Liberali (2013), articulated to the linguistic-discursive aspects of the manifestations of contradictions, such as Engeström and Sannino (2011), Magalhães and Ninin (2016). The results showed these contradictions: reading proposal with didactic focus unrelated to the reading expertise of the participants; reading proposal and 1st meeting plan with aspects of socio-historical-cultural approach just in the name, but focused on theoretical aspects; performance activity configured in the plane of ideas; duality between theory and practice; lack of establishment of difference between the type of reading understood by the participants and a new mode; teaching-learning relationship focused on specific needs by the students and theoretical knowledge by the teacher-researcher; critical-collaborative perspective of the discussion centered on the teacher's role; reading limited to four social functions, despite the multiform reality of human activity; teaching-learning of reading by fragments of discourse genres; reading with theoretical approach to the development of specific knowledge; reading as a reproduction of the author's ideas; reading time just like the action of reading; reductionist view of the concept of Multiletramentos. Such contradictions were related to the participants of this research, and they were evident in the meetings between the different historical constitutions of these participants and in their insertion in a new type of reading study environment in the Study Group